Effects of a 12-week dance intervention on left-behind children with co-occurring social anxiety and low self-concept - Li, Xiaolin; Yang, Qian; Zhou, Zhenqian; Zeng, Ming; Lu, Chunxia; Dong, Weixin (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to investigate the effects of a 12-week dance intervention on left-behind children (LBC) suffering from social anxiety and low self-concept, and to explore the relationship between social anxiety and self-concept.MethodsSixty LBC who met the criteria were selected from a school in Shaoyang City, Hunan Province, and were randomly divided into an Interventional group (n = 30) and a Control group (n = 30). The Interventional group received a 45-min dance intervention five times a week for 12 weeks, while the Control group maintained their original lifestyle. Social anxiety and self-concept were measured three times using the Social Anxiety Scale for Children and the Piers-Harris Child Self-concept Scale: at baseline (T0), post-intervention (12 weeks, T1), and follow-up (14 weeks after baseline, T2).Results(i) After the dance intervention, social anxiety and self-concept were significantly improved (p < 0.05). (ii) There was a significant negative correlation between the change scores (T1 minus T0) of social anxiety and self-concept (p < 0.05).ConclusionDance intervention is an acceptable, practical and effective intervention that we can incorporate into a health programme to improve social anxiety and low self-concept in LBC.